MENINGKATKAN KEMAMPUAN MENGENAL HURUF MELALUI BERMAIN KOTAK HURUF DI KELOMPOK B2 TK PEMBINA NEGERI 1 BANGKO KABUPATEN ROKAN HILIR - Damanik, Juli Hartati; Zulkifli N, Zulkifli N; Nurlita, Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Background of this study is the lack of ability of children to recognize letters. Some children are still undeveloped in differentiating vocal and consonant letters, children still like to mention the letters upside down in almost the same shape and sound and some children may not thrive in naming and grouping images - pictures or objects that have the same initial letters as well as in understanding between the sound and the shape of the letter. Under these conditions it is necessary to attempt to improve the child's ability to know the letter Playing namely through letter box, type this research is action research class conducted in two (2) cycles. Data collectors instrument used in this study is the form of sheets of observation and research subjects are Group B2 consisting of 10 People Boys - Boys and Girls 7 people. Results showed Improvement of Cycle I to Cycle II. Improvement occurred, ie from before the action to the first cycle of 30.35%, Cycle I Cycle II Into amounted to 42.18% and from before Cycle II Amounting to 85.33%. From the results of this study concluded that through the letter box play can enhance the ability recognize letters kindergarten in B2 group Pembina State 1 bangko Rokan Hilir.Keywords: Recognize Letters, Playing the letter box.